Implementasi Euthanasia dalam Perspektif Ulama dan Hak Asasi Manusia - Warjiyati, Sri (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2020)
Euthanasia is a problematical issue among doctors, legal practitioners, and religious scholars. It has become a topic of discussion in various countries, especially Indonesia and Malaysia when viewed from the perspective of religion and human rights. The scholars agree that an action can only be classified as a Jarimah if the action is strictly prohibited by syara'. Although there is no clarity or certainty in determining whether euthanasia is a crime or not, the concept of euthanasia itself, formulated by experts, is written and is prohibited in the Al-Quran and Hadith. For example in the Al-Qur'an in QS. Al-An'am verse 151: